Analisis Harga dan Keuntungan Usahatani Nilam di Desa Benua Kecamatan Benua Kabupaten Konawe Selatan - Wulandari, Restian; Rianse, Usman; Abdullah, Weka Gusmiarty (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2018)
This study aims to determine the condition of prices and benefits of patchouli farming in Benua District, South Konawe Regency. Determination of samples using the Slovin formula with an error tolerance limit of 5% so that a sample of 60 farmer respondents was obtained. Analysis of the data used is descriptive analysis and profit analysis. The results showed that the difference in selling prices of dried patchouli in Benua District, South Konawe Regency was due to the different buyers and quality of patchouli. Patchouli quality is influenced by farmers' management abilities and different harvesting frequencies. While the level of profits obtained by patchouli farmers in Benua Subdistrict, Konawe Selatan Regency are mostly in the low category (90.00%) and only 6.67% in the high category